The Use of Large-Particle Aerosol Exposure to Nipah Virus to Mimic Human Neurological Disease Manifestations in the African Green Monkey. (5th November 2019) - Lee, Ji Hyun; Hammoud, Dima A; Cong, Yu; Huzella, Louis M; Castro, Marcelo A; Solomon, Jeffrey; Laux, Joseph; Lackemeyer, Matthew; Bohannon, J Kyle; Rojas, Oscar; Byrum, Russ; Adams, Ricky; et al.
Abstract: Nipah virus (NiV) is an emerging virus associated with outbreaks of acute respiratory disease and encephalitis. To develop a neurological model for NiV infection, we exposed 6 adult African green monkeys to a large-particle (approximately 12 μm) aerosol containing NiV (Malaysian isolate). Brain magnetic resonance images were obtained at baseline, every 3 days after exposure for 2 weeks, and then weekly until week 8 after exposure. Four of six animals showed abnormalities reminiscent of human disease in brain magnetic resonance images. Abnormalities ranged from cytotoxic edema to vasogenic edema. The majority of lesions were small infarcts, and a few showed inflammatory or encephalitic changes. Resolution or decreased size in some lesions resembled findings reported in patients with NiV infection. Histological lesions in the brain included multifocal areas of encephalomalacia, corresponding to known ischemic foci. In other regions of the brain there was evidence of vasculitis, with perivascular infiltrates of inflammatory cells and rare intravascular fibrin thrombi. This animal model will help us better understand the acute neurological features of NiV infection and develop therapeutic approaches for managing disease caused by NiV infection.